2018
DOI: 10.7150/ijbs.24032
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide Attenuates Renal Tubular Epithelial-mesenchymal Transition Via the MiR-188-5p-mediated PI3K/AKT Pathway in Diabetic Kidney Disease

Abstract: Triptolide possesses the trait of renal protection. Epithelial-mesenchymal transition (EMT) is closely linked to the pathogenesis of diabetic kidney disease (DKD). MicroRNAs have recently emerged as critical regulators of DKD. However, it is poorly understood whether triptolide alleviates renal EMT by regulating microRNAs in DKD. In this study, we found that triptolide decreased albuminuria, improved the renal structure and reduced renal EMT in rats with DKD. Furthermore, activation of the PI3K/AKT signaling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 46 publications
2
66
0
Order By: Relevance
“…TPL has anti-inflammatory, anti-tumor, and immunologic effects on many diseases [4]. TPL inhibits the secretion of many cytokines, adhesion molecules, and chemokines and affects the functions of various cells, including dendritic cells and renal tubular epithelial cells [5,6]. TPL has been reported to alleviate the progression of glomerulosclerosis and the excretion rate of urinary albumin to inhibit the progression…”
Section: Introductionmentioning
confidence: 99%
“…TPL has anti-inflammatory, anti-tumor, and immunologic effects on many diseases [4]. TPL inhibits the secretion of many cytokines, adhesion molecules, and chemokines and affects the functions of various cells, including dendritic cells and renal tubular epithelial cells [5,6]. TPL has been reported to alleviate the progression of glomerulosclerosis and the excretion rate of urinary albumin to inhibit the progression…”
Section: Introductionmentioning
confidence: 99%
“…In a cell culture model, miR-188-5p is shown to regulate high glucose-induced epithelial-mesenchymal transition (EMT) in human proximal tubular cell lines through the PTEN/PI3K/Akt pathway [21]. By analyzing miRs from the patients' urine exosomes, we demonstrated the pathologic role of miR-188-5p in nephrotic and biopsy-proven isolated DN.…”
Section: Discussionmentioning
confidence: 95%
“…The strongest up-regulation that we identified in the urine exosomes of the nephrotic, isolated DN patients was with miR-188-5p. This miR has been reported to regulate the high glucose-induced epithelial-mesenchymal transition of HK-2 cells through the PTEN/PI3K/Akt pathway [21]. The second most strongly up-regulated miR was miR-150-3p.…”
Section: Urinary-exosomal Mir Signaturesmentioning
confidence: 93%
“…miR-93 was related with insulin resistance [30] and it was observed that plasma level of miR-93-3p was associated with higher risk to develop type 2 diabetic in human [31]. The expression of miR-188-5p increased in human proximal tubular epithelial (HK-2) cells stimulated by high glucose level [32]. The current state of evidence for the relationship between miR-466k, miR-1188-5p, miR-7001-3p, miR-7115-5p and diabetes has so far been unknown.…”
Section: Discussionmentioning
confidence: 99%